Energy optimization of air distribution and chilled water systems - Zhang, Ling (2008)
Currently, the most popular HVAC systems in large commercial buildings are chilled water systems, and the primary-secondary pumping chilled water loop is a tool that the HVAC engineers have been using for nearly 50 years. In this dissertation, we will only discuss the energy optimization for air distribution and chilled water systems of large HVAC systems.